Proceedings of the Canadian Frailty Network Summit: Medication Optimization for Frail Older Canadians, Toronto, Monday April 24, 2017. - Muscedere, John; Kim, Perry; Aitken, Peter; Gaucher, Michael; Osborn, Robin; Farrell, Barbara; Holroyd-Leduc, Jayna; Mallery, Laurie; Siu, Henry; Downar, James; Lee, Todd C.; McDonald, Emily; et al. (Canadian Geriatrics Journal, 2017)
Appropriate and optimal use of medication and polypharmacy are especially relevant to the care of older Canadians living with frailty, often impacting their health outcomes and quality of life. A majority (two thirds) of older adults (65 or older) are prescribed five or more drug classes and over one-quarter are prescribed 10 or more drugs. The risk of adverse drug-induced events is even greater for those aged 85 or older where 40% are estimated to take drugs from 10 or more drug classes. The Canadian Frailty Network (CFN), a pan-Canadian non-for-profit organization funded by the Government of Canada through the Networks of Centres of Excellence Program (NCE), is dedicated to improving the care of older Canadian living with frailty and, as part of its mandate, convened a meeting of stakeholders from across Canada to seek their perspectives on appropriate medication prescription. The CFN Medication Optimization Summit identified priorities to help inform the design of future research and knowledge mobilization efforts to facilitate optimal medication prescribing in older adults living with frailty. The priorities were developed and selected through a modified Delphi process commencing before and concluding during the summit. Herein we describe the overall approach/process to the summit, a summary of all the presentations and discussions, and the top ten priorities selected by the participants.